Pure Bending of the Orthotropic Elastic Rectangle - Kravchuk, M.; Nagórko, W.; Podhorecki, A. (Engineering Transactions, 2015)
In this contribution, a new method for obtaining the solution to the linear elasticity problem is proposed. An idea of this method is based on certain special expansion of these displacement fields in finite trigonometric series with exponential coefficients. This approach leads to an equivalent problem which requires to derive the exact solution. The proposed method has a mixed analytic-numerical form and has been illustrated by the solution to the boundary value problem for a rectangular region subjected to bending by loads applied on the opposite sides of the region. The numerical results derived have been compared with solutions obtained in the framework of the Euler–Bernoulli beam theory.